Toxoplasma exports dense granule proteins beyond the vacuole to the host cell nucleus and rewires the host genome expression. (20th January 2014) - Bougdour, Alexandre; Tardieux, Isabelle; Hakimi, Mohamed‐Ali
Summary T oxoplasma gondii is the most widespread apicomplexan parasite and occupies a large spectrum of niches by infecting virtually any warm‐blooded animals. As an obligate intracellular parasite, Toxoplasma has evolved a repertoire of strategies to fine‐tune the cellular environment in an optimal way to promote growth and persistence in host tissues hence increasing the chance to be transmitted to new hosts. Short and long‐term intracellular survival is associated with Toxoplasma ability to both evade the host deleterious immune defences and to stimulate a beneficial immune balance by governing host cell gene expression. It is only recently that parasite proteins responsible for driving these transcriptional changes have been identified. While proteins contained in the apical secretory Rhoptry organelle have already been identified as bona fide secreted effectors that divert host signalling pathways, recent findings revealed that dense granule proteins should be added to the growing list of effectors as they reach the host cell cytoplasm and nucleus and target various host cell pathways in the course of cell infection. Herein, we emphasize on a novel subfamily of dense granule residentproteins, exemplified with the GRA16 and GRA24 members we recently discovered as both are exported beyond the vacuole‐containing parasites and reach the host cell nucleus to reshape the host genome expression.